Effects of presession well-being perception on internal training load in female volleyball players - Ungureanu, A. N.; Brustio, P. R.; Boccia, G.; Rainoldi, A.; Lupo, C. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To evaluate if the internal training load (ITL; Edwards heart rate [HR]-based and session-rating of perceived exertion [RPE] methods) is affected by the presession well-being perception, age, and position in elite (ie, Serie A2) female volleyball training.